2017
DOI: 10.3389/fonc.2017.00163
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Bone Metastases of Breast, Lung, and Prostate Cancers: Do Bone Homing Cancers Favor Feminized Bone Marrow?

Abstract: Sex-associated differences in bone metastasis formation from breast, lung, and prostate cancer exist in clinical studies, but have not been systematically reviewed. Differences in the bone marrow niche can be attributed to sexual dimorphism, to genetic variations that affect sex hormone levels, or to the direct effects of sex hormones, natural or exogenously delivered. This review describes the present understanding of sex-associated and sex hormone level differences in the marrow niche and in formation of bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 96 publications
2
13
1
Order By: Relevance
“…Although, to date, no significant association has been reported by others between organ preference and gender, it is suspected that organ preference is most likely attributable to a combination of hormonal regulation and underlying biology related to sexual dimorphism. [27][28][29][30] However, our results regarding age distribution and metastatic spread are in line with others since we also found that brain metastases appeared more frequently in the younger population and bone metastases among elderly patients. [30][31][32] A possible explanation might be that brain metastases are associated with the angiogenic microenvironment, and the cerebrovascular microenvironment factors of young patients may be better than those of older patients, while in the case of bone metastases the more favorable bone marrow microenvironment for metastatic spread and the higher incidence of osteoporosis in elderly patients might contribute to the higher incidence of bone metastases.…”
Section: Discussionsupporting
confidence: 92%
“…Although, to date, no significant association has been reported by others between organ preference and gender, it is suspected that organ preference is most likely attributable to a combination of hormonal regulation and underlying biology related to sexual dimorphism. [27][28][29][30] However, our results regarding age distribution and metastatic spread are in line with others since we also found that brain metastases appeared more frequently in the younger population and bone metastases among elderly patients. [30][31][32] A possible explanation might be that brain metastases are associated with the angiogenic microenvironment, and the cerebrovascular microenvironment factors of young patients may be better than those of older patients, while in the case of bone metastases the more favorable bone marrow microenvironment for metastatic spread and the higher incidence of osteoporosis in elderly patients might contribute to the higher incidence of bone metastases.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in contrast with a recent review which concluded that for lung cancer females might have a more favorable bone microenvironment for metastasis formation [51]. Anyhow, the differences could possibly be the result of statistical variation.…”
Section: Resultscontrasting
confidence: 90%
“…Moreover, androgens are thought to contribute directly to male periosteal bone expansion, mineralization, and trabecular bone maintenance, which are important in the pathogenesis of BM [26, 27]. The latest review suggested that hormonal status affected the occurrence of BM [28]. In our study, the relationship between the occurrence of BM and age was in contrast with the tendency of human sex hormone levels to change with age [29].…”
Section: Discussionmentioning
confidence: 70%